Communication and Crime Prevention from Psychological Point of View - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Suffering a perceived or real victimization could be recorded as a serious traumatic event in the life of a person. However, it is important to emphasize that the chapter does not only focus on the victims of norm-violating human behaviour or crimes, but on all human conflicts where the person concerned identifies themselves as victims. (e.g. peer-group conflicts, toxic family relationships, burdensome parenting methods)The impact of this is not only related to the course of formal proceedings. Becoming an “actor” in the judiciary can be accompanied by serious psychological pressure, stress and anxiety. To experience during the formal procedure, that there is no opportunity to share the most important psychological effects, but at the same time, to experience different new negative feelings, not only cause reliving previous events, but can even lead to new traumatization (or becoming a repeat victim). Spiritual reassurance and psychological satisfaction are lacking, as even the faith in world- just-hypothesis and in the existence of control over our own fate is broken. The person does not understand why all this happened to them – but they do not immediately receive an answer to their question.The aim of the chapter is to present what human needs are violated in a victim situation, and to what extent and why communication-focused transformative mediation can help to free oneself from the negative effects of victimization through their restoration.Keywords: victimization, negative effects of toxic relationships, human needs, Maslow-pyramid, transformative mediation, communication